Distribusi Unsur Hara Kalium Tanah dan Kadarnya pada Tanaman Padi Sawah di Wilayah Sub Das Serayu Hilir Kecamatan Sampang Kabupaten Cilacap - Dewi, Fitria Aninda; Widyasunu, Purwandaru; Maryanto, Joko (Proceedings Series on Physical & Formal Sciences, 2021)
This study aims to determine: (1) distribution of soil potassium nutrients in paddy fields in Serayu Watershed Downstream, Sampang District, Cilacap Regency, (2) distribution of soil potassium nutrient availability, K-content in plant tissue with rice yields in Serayu Watershed Downstream, Sampang District, Cilacap Regency, and 3) fertilizer recommendations potassium in paddy soil in Serayu Watershed Downstream, Sampang District, Cilacap Regency. The study method was conducted by determining 9 sample points by the making of SLH (Homogeneous Land Unit) map with a scale of 1:50.000 by overlaying the Sampang Disctrict Administration Map, the Soil Type Map, the Slope Map, and the Land Use Map. The variables mesured were pH H2O, pH KCl, DHL (electrical conductivity), redox potential, K-available, K-content in plant tissue, climatic conditions, plant varieties, and wet grain rice yields. The results showed that the distribution of potassium nutrients in Sampang District had a low status. The paddy varieties cultivated during research in Sampang District consist of Ciherang, HT Logawa, Inpari 32, and IR64. The climatic condition of Sampang District is the optimal climates for paddy cultivation. The best correlation result with crop yield was between K-available and crop yield. The value of K-available has a determinant coefficient of 47.37% of the yield of rice, while the K content in plant tissue has 19.45% of the yield of rice. Fertilizing recommendations in the research area is 87.73 kg K2O/ha or equivalent to an average of 175.47 kg KCl/ha.